Colonial seeds in African soil : a critical history of forest conservation in Sierra Leone - Munro, Paul, 1958- (Environment in history ;, 2020)
""Empire forestry"--The broadly shared forest management practice that emerged in the West in the nineteenth century-may have originated in Europe, but it would eventually reshape the landscapes of colonies around the world. Melding the approaches of environmental history and political ecology, Colonial Roots in African Soil unravels the complex ways this dynamic played out in twentieth-century colonial Sierra Leone. While giving careful attention to topics such as forest reservation and exploitation, the volume moves beyond conservation practices and discourses, attending to the overlapping social, economic, and political contexts that have shaped approaches to forest management over time"--